Studi Etnofarmasi Tumbuhan Berkhasiat Obat pada Ibu Nifas di Desa Batu Timbau Kutai Timur - Devanty Fadilla; Nur Masyithah Zamruddin; Laode Rijai (PT Bukuloka Literasi Bangsa, 2026)
Ethnopharmacy is a branch of science that studies the use of traditional medicine based on local knowledge passed down through generations. Indonesia has high biodiversity and cultural diversity, providing great potential for the utilization of medicinal plants, particularly in postpartum care. This study aims to identify and document the use of medicinal plants among postpartum mothers of the Kutai ethnic group in Batu Timbau Village, Batu Ampar District, Kutai Timur Regency, Kalimantan Timur. This research employed a qualitative descriptive method, with data collected through observation, semi-structured interviews, and documentation using purposive sampling involving 35 postpartum mother informants. Data were analyzed qualitatively and quantitatively using Use Value (UV) analysis to determine the relative importance of each species based on its frequency of use.The results showed that the community utilizes medicinal plants from 29 families, predominantly the Zingiberaceae family, for postpartum care. The plants are used as single preparations or in combinations to accelerate postpartum recovery, reduce pain, increase stamina, support uterine involution, and enhance breast milk production. The plant with the highest UV value is katuk leaf (0.714), indicating its high relative level of use among the studied community. Keywords: ethnopharmacology, medicinal plants, postpartum women, traditional medicine, Use Value.